Issues and Challenges of Class C Contractors in Pokhara - Gurung, Hem Prasad; KC, Brijendra (Technical Journal, 2023)
This study entitled “Issues and Challenges of Class C Contractors in Pokhara” was carried out for all Class C Contractors registered in Contractors’ Association of Nepal (CAN) Kaski. This study aims to investigate the issues and challenges faced by Class C contractors in Pokhara. Expert interview were conducted after thoroughly reviewing the literature and reports of the Nepalese construction industry to identify the major problems of Nepalese contractors. The data were collection through questionnaire surveys and interviews. The main objective was to identify the burning issues and challenges of Class C contractors of Pokhara.The findings revealed that most of the construction firms in Pokhara are engaged in different sectors of constructions and few firms are specialized in particular construction work i.e. Road construction and maintenance. These firms meet equipment capacity as per CBA 2055 & CBR 2056 and are financially and technically viable for bidding process as per Qualification Criteria of PPA 2063 & PPR 2064. The results indicated that the major issues and challenges of contractors in Pokhara are competitive pre-qualification process during bidding, low bidding and corruption, hiring qualified human resources, work experience, delay in payment, political intervention, job insecurity, price escalation and inflation, insecurity due to hooliganism in construction site, revenue and taxation, government rules and regulations, contract documents, etc. Based on the findings of the study, it is concluded that the government and concerned authorities should implement flexible and appropriate policies and laws with standard guidelines for prequalification criteria and formulate amendments in standard bidding documents containing clauses under new procurement act. Amendments like bidding capacity of classified contractors, price escalation and inflation, JV prequalification criteria, duty privilege for construction equipment, high rate of registration, renewable fee and vehicle tax, VAT system, present income tax assessment procedure, etc. should be revised under new procurement act. The study can also be useful for benchmarking the status of Class C Contractors in Pokhara.